2002
DOI: 10.7182/prtr.12.2.y334106037764778
|View full text |Cite
|
Sign up to set email alerts
|

Posttransplant viral syndromes in pediatric patients: a review

Abstract: The success of pediatric solid organ transplantation has been largely due to advancements in surgical techniques, technology, and preoperative and postoperative care. Potent immunosuppression continues to reduce the incidence and severity of rejection, and improve long-term survival. However, there is growing awareness of the role immunosuppression plays in contributing to the incidence of cytomegalovirus, Epstein-Barr virus, and Epstein-Barr virus-associated posttransplant lymphoproliferative disease. Herpes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…34,51 A recent review found that the incidence of PTLD in the pediatric transplant population has been reported to be as high as 10% in heart transplant recipients, 22% in lung transplant recipients, 20% in liver recipients, and up to 40% in patients with multivisceral grafts. 52 Another study reported a PTLD frequency of 10.1% in a pediatric kidney transplant population compared with a PTLD frequency of 1.2% in an adult kidney transplant population. 53 Of pediatric PTLD cases reported to the IPITTR, 61% received nonkidney transplants.…”
Section: Pediatric Patients At Greater Risk Than Adultsmentioning
confidence: 98%
“…34,51 A recent review found that the incidence of PTLD in the pediatric transplant population has been reported to be as high as 10% in heart transplant recipients, 22% in lung transplant recipients, 20% in liver recipients, and up to 40% in patients with multivisceral grafts. 52 Another study reported a PTLD frequency of 10.1% in a pediatric kidney transplant population compared with a PTLD frequency of 1.2% in an adult kidney transplant population. 53 Of pediatric PTLD cases reported to the IPITTR, 61% received nonkidney transplants.…”
Section: Pediatric Patients At Greater Risk Than Adultsmentioning
confidence: 98%